Computational modelling of the biosensor acting under parallel substrates conversion with dialysis membrane - Ašeris, Vytautas (Lietuvos matematikos rinkinys, 2012)
A mathematical model of biosensor acting under parallel substrates conversion is investigated in this paper. Model consists of reaction-diffusion equations with non-linear terms, which in general case are solved numericaly. The mathematical model describes biosensor action in one-dimensional space, which consists of enzymatic, dialysis and diffusion layers. The purpose of this work was to define for which parameter values the layers of diffusion and dialysis membrane can be replaced by one external layer, described by the effective diffusion coefficient. The simulation error of two-layered model response was investigated by comparing it to the values of three-layered model response.
Keywords: biosensor; parallel substrates conversion; mathematical modelling; effective diffusion coefficient; finite difference scheme